2012
DOI: 10.1161/circresaha.111.253419
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Nitric Oxide Prevents Ischemic Brain Damage in Experimental Stroke by Selective Dilatation of Collateral Arterioles

Abstract: Rationale: Stroke is the third most common cause of death in industrialized countries. The main therapeutic target is the ischemic penumbra, potentially salvageable brain tissue that dies within the first few hours after blood flow cessation. Hence, strategies to keep the penumbra alive until reperfusion occurs are needed.Objective: To study the effect of inhaled nitric oxide on cerebral vessels and cerebral perfusion under physiological conditions and in different models of cerebral ischemia. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
134
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(163 citation statements)
references
References 65 publications
12
134
3
2
Order By: Relevance
“…4-Amino-5-methylamino-2',7'-difluorofluorescein diacetate (Molecular Probes) was topically applied (concentration: 50 to 200 μmol/l, 30 minutes incubation) 18 before PT for baseline imaging and ∼ 3 hours after PT to detect NO (n = 5).…”
Section: Intravital Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…4-Amino-5-methylamino-2',7'-difluorofluorescein diacetate (Molecular Probes) was topically applied (concentration: 50 to 200 μmol/l, 30 minutes incubation) 18 before PT for baseline imaging and ∼ 3 hours after PT to detect NO (n = 5).…”
Section: Intravital Fluorescence Imagingmentioning
confidence: 99%
“…Despite the recent development of new small molecule indicators, most data still originate from in vitro models. 48 Recently, DAF-FM was successfully used to detect NO formation in the arterial and venous cerebral circulation after transient medial cerebral artery occlusion in the mice brain in vivo, 18 yet it is still to be uncovered which cells produce NO. 24 We report increased NO levels in the peri-ischemic brain, mostly in close vicinity to the arterial wall, suggesting a major nonneuronal contribution to NO formation.…”
Section: Pt 3hmentioning
confidence: 99%
“…Nitric oxide inhalation is a clinically approved treatment that has few side effects that might positively influence the outcome following ischemic stroke. Terpolilli et al (2011) recently demonstrated an effect of iNO on the cerebrovasculature using in vivo microscopy. In their studies under physiological conditions, iNO led to a significant dilatation of cerebral venules, most probably due to an oxygentension-dependent mechanism.…”
Section: Inhaled Nitric Oxide Donorsmentioning
confidence: 99%
“…On the other hand, NO is also used as a medical treatment, such as for the treatment of newborn infants with hypoxemic respiratory failure (5) and to prevent ischemic stroke. (6) Therefore, many techniques, such as chemiluminescence (7) and electron paramagnetic resonance (EPR) spectroscopy, (8) have been developed. Although these methods can detect NO in the nM range, they cannot be applied to in vivo research owing to toxicity from chemical reactions and the large size of the equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In small animals, this method is widely used for NO detection. For example, Terpolilli et al (6) studied the functions of NO to prevent ischemic brain damage. However, it is difficult for use in the long-term detection of NO in animals because of the restriction of a microscope, which requires a fixed area and is bulky in size.…”
Section: Introductionmentioning
confidence: 99%